2018
DOI: 10.3892/ol.2018.9068
|View full text |Cite
|
Sign up to set email alerts
|

Optimal body mass index cut‑point for predicting recurrence‑free survival in patients with non‑muscle‑invasive urothelial carcinoma of bladder

Abstract: In Japanese patients with non-muscle-invasive urothelial carcinoma of the bladder, the impact of body mass index (BMI) on recurrence following transurethral resection of bladder tumor (TURBT) is unclear. The present study retrospectively examined data collected from 50 patients diagnosed with primary urothelial carcinoma of the bladder (pTa, pTis, and pT1) who had previously undergone TURBT surgery. Two BMI cut-off points for predicting disease recurrence were evaluated: i) A threshold generated through receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…Among NMIBC patients, the majority of studies suggest that elevated BMI is associated with increased risks of recurrence [ 7 , 24 , 34 , 65 , 66 , 73 , 74 ] and progression [ 65 , 66 , 73 , 74 ]. The association between BMI and recurrence is more conflicting in studies with both NMIBC and MIBC patients [ 7 , 25 , 30 , 68 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among NMIBC patients, the majority of studies suggest that elevated BMI is associated with increased risks of recurrence [ 7 , 24 , 34 , 65 , 66 , 73 , 74 ] and progression [ 65 , 66 , 73 , 74 ]. The association between BMI and recurrence is more conflicting in studies with both NMIBC and MIBC patients [ 7 , 25 , 30 , 68 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies have assessed the association between body mass index (BMI) and prognosis [7,24,25,30,34,39,59,[65][66][67][68][69][70][71][72][73][74][75]. One study assessed BMI at diagnosis, [24] 13 studies assessed BMI at time of treatment (e.g., transurethral resection of bladder tumor (TURBT), radical cystectomy), [25,30,34,39,59,[65][66][67][68][69][70][71][72] and three studies did not report timing of BMI measurement [73][74][75].…”
Section: Body Mass Indexmentioning
confidence: 99%
“…Several studies indicated that PNLR was associated with an increased risk of disease recurrence, progression and survival in patients with NMIBC [ 17 18 22 ]. However, none of these studies focused on the effectiveness of PNLR in VH-NMIBC.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicated that the appearance of VH in NMIBC usually meant advent disease and poor prognosis, prompting surgeons to perform early RC [ 22 ]. Urologists sought to determine what patient subset has aggressive properties and discover the useful biomarkers for identifying a higher risk population, especially in patients with VH-NMIBC.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited and inconsistent evidence regarding the association between obesity and risk of NMIBC recurrence and progression. Seven cohort studies showed that higher body mass index (BMI) was associated with higher risk of recurrence, 7–13 of which five studies showed statistically significant associations 7–11 . In contrast, two studies reported no associations 14,15 .…”
Section: Introductionmentioning
confidence: 99%